Design and analysis of multi-cavity traditional and H-branching runners for plastic injection mold - Hamsin, M.R.; Azuddin, M.; Ahmad-Yazid, A. (The Institution of Engineers Malaysia, 2009)
This paper describes the design and analysis of plastic injection mold balancing runner. The runners were designed based on Ellis Model, a viscosity model of flow network consisting of elements and nodes. 4-coefficients viscosity model and temperature dependence Ellis Model were used in order to reduce the amount of computational analysis by FEA software. A Cross WLF viscosity model was used in the FEA analysis. FEA simulation of injection molding was conducted for 8 and 16 cavity runners. Runner layout was assumed as pressure at the end of each element acting as an initial and final boundary condition. The length and size of the runner can be adjusted to fit the boundary condition that had been chosen. Flow rates at each element leading to gates were set to simulate the desired pressure drop. The final boundary condition for the first element was set as the initial boundary condition for the next element. By employing Ellis model, it was shown that the calculated results are similar to the result obtained through simulation. The model employed has successfully shown an equal filling time for each cavity, an equal pressure at each gate as well as uniform part filling. A predictive FEA performed prior to actual manufacturing is helpful in order to produce good molds.